Z zagadnień bezpodstawnego wzbogacenia w prawie węgierskim: [Groundless enrichment in the Hungarian law] (Studia Prawnicze / The Legal Studies, 1983)
The work systematically presents the institution of groundless enrichment in the Hungarian legal system. In part I (general legislative and constructive characteristics) relations between condictions, provisions on settlements owner-possessor, and provisions on the redress of damage have been presented as well as the possibilities in which provisions on groundless enrichment can be applied (the Hungarian law considers conditions as strictly subsidiary claims); their application is limited and their importance is diminishing). Part II (premises of groundless enrichment) discusses notions of enrichment, empoverishment, relation between them (genetic not causal) and the lack of legal ground. In this part negative premises of condiction have been discussed (loss of the object of enrichment without substitute), spending on alimony obligation - even when the person enriched had known of the obligation to return. The Hungarian law expands obligations of the person enriched in bad faith and of that who should be prepared for the return of enrichment - these matters have also been discussed in Part II.In Part III (object and scope of the obligation to return) the principle (as well as consequences) of the return of actual enrichment has been discussed as well as the return of profits, settlement of accounts resulting from the damage caused to the object of enrichment. The Hungarian law provides for two principles in solving these matters: a person managing his property cannot bear negative consequences of his behaviour only because later on it turned out that he had not been the owner, and - comprised in Art. 4 para. 4 of the Civil Code a modernized rule - nemo auditur propriam turpitudinem allegans. These rules explain the Hungarian formulation which provides for the forfeiture of the object of enrichment on behalf of the State in case when the enrichment is a result of foul deed (turpitudo). It should be noted that Hungarian courts which pass decisions can freely decide on the proportions of return (forfeiture). Both the forfeiture of the enrichment as well as settlement by way of execution of an invalid contract, separately regulated in the Civil Code are not cases of groundless enrichment in the strict meaning, although they are inspired by the same legislative thought. The above problems have been discussed in Part IV.